Pengaruh Penggunaan Digital Banking Sebagai Layanan Transaksi Online Terhadap Kepuasan Nasabah Bank Sumut Syariah KCP HM Joni - Mutiara Yolanda; Waizul Qarni (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to determine the extent of the influence of the use of digital banking as an online transaction service on customer satisfaction of Bank Sumut Syariah Kcp Hm Joni with a focus on the variables Accurancy (X1), Speed (X2), Security (X3). This study uses a quantitative approach with sampling using the non-probability sampling method. The type of data used in this study is Primary Data obtained from questionnaires filled out by respondents directly. And Secondary data derived from books, journals, research results, practical work reports and related to the author's research object. In this study, the population to be taken is all North Sumatra Syariah KCP HM Joni customers in 2022 as many as 21,500 people. The analysis tool uses multiple linear regression analysis. The results showed that the variables Accurancy (X1), Speed (X2), Security (X3) simultaneously affect the satisfaction of customers using digital banking Sumut Syariah KCP HM Joni. The coefficient of determination is 0.741. This means that 74.1% of bank existence is influenced by Accurancy (X1), Speed (X2), and Security (X3), while the remaining 25.9% of customer satisfaction is influenced by other variables not examined in this study.